Pelaksanaan "Aplikasi Woka Abt" untuk Penilaian Efisiensi di Sekolah Menengah Atas - Adi Nuryadi; EL Rakhmah; EL Rokhmah; Muhamad Ikmal Alhudawi (Jurnal Syntax Admiration, 2024)
In the rapidly developing digital era, the application of technology in the field of education is a must to improve the quality and efficiency of the learning and assessment process. One of the innovations that has emerged is the use of Android-based applications for the implementation of exams and assessments. This study aims to analyze the use of the Woka ABT (Android Based Test) application in improving the efficiency of final semester assessments at SMA Negeri 2 Garut. Along with the development of technology, digital-based assessment methods are increasingly needed to replace conventional assessments that take more time and resources. This study uses a quantitative approach with an experimental method. Data was collected through surveys and interviews with teachers as well as analysis of time and costs incurred before and after the use of the Woka ABT application. The results show that the use of the Woka ABT application significantly reduces the time required for the assessment process and processing of exam results. In addition, the application also reduces paper usage and operational costs, as well as improves accuracy in assessment. Teachers and students have given positive feedback to the use of this application because of the ease of access and features that help in the teaching and learning process. The conclusion of this study is that the implementation of the Woka ABT application at SMA Negeri 2 Garut contributes positively to the efficiency of the final semester assessment. The implementation of Android-based technology in educational assessment not only improves efficiency, but also supports schools' efforts towards wider digitalization. The recommendation of this study is that other schools can consider using similar applications to improve efficiency and effectiveness in the assessment process.